2020
DOI: 10.3390/medicina56110604
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of Dietary Antioxidants on Cervical Cancer Development

Abstract: Cervical cancer results from a continuous process, starting from a normal cervical epithelium after human papillomavirus (HPV) infection and progressing to cervical intraepithelial neoplasia (CIN), before finally developing into invasive squamous carcinoma (ISC). In recent decades, dietary antioxidants, such as vitamins, have received much attention in relation to cancer prevention. We reviewed the relevant literature to investigate the dietary and nutrient intake on cervical cancer. The intake of vitamins A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…They suggested that the intake of vitamin A, carotenoids, and vitamin D may inhibit cervical cancer development at early stages. Conversely, the intake of vitamin C and E may be useful in the inhibition of the cervical cancer development process [ 197 ], while vitamin A’s main effect is inhibition of HPV infection and CIN development [ 188 ]. In 2000, Yeo.…”
Section: Gynecological Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the intake of vitamin A, carotenoids, and vitamin D may inhibit cervical cancer development at early stages. Conversely, the intake of vitamin C and E may be useful in the inhibition of the cervical cancer development process [ 197 ], while vitamin A’s main effect is inhibition of HPV infection and CIN development [ 188 ]. In 2000, Yeo.…”
Section: Gynecological Cancersmentioning
confidence: 99%
“…To conclude, several nutrients with antioxidant effects may present potent abilities to intervene in the natural history of cervical cancer tumorigenesis connected with HPV infection [ 197 ]. Selected vitamins (such as vitamins A and D) and natural compounds (e.g., EGCG) demonstrate a positive effect in halting the cervical cancer disease process.…”
Section: Gynecological Cancersmentioning
confidence: 99%
“…Eating vegetables and fruit containing a significant number of vitamins may contribute to inhibition of cervical cancer development. Special attention is focused on vitamins C and E, as well as influence of B vitamins, vitamin A and D [6]. Unfortunately, the respondents in the own study, in majority, did not have the knowledge on this topic and vitamins deficiencies were not often considered as risk factors by them (Figure 2).…”
Section: Resultsmentioning
confidence: 96%
“…Cervical cancer risk factors include age, early onset of sexual intercourse, big number of sexual partners, [12], highly processed food and vitamins deficiencies [6], smoking cigarettes [7], oral hormonal contraception [8], intimate infections [9], disorders of the vaginal flora [10], number of births [11] and persistent human papillomavirus infection [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation